The Population Structure of Endemic Halmahera Walking Shark (Hemiscyllium halmahera, Allen 2013) in Kao Bay Sea, North Maluku, Indonesia - Akbar, Nebuchadnezzar; Bengen, Dietriech Geoffrey; Nurjaya, I Wayan; Natih, Nyoman MN; Baksir, Abdurrachman; Subhan, Beginer; Arafat, Dondy; Ismail, Firdaut; Siolimbona, Abdul Ajiz; Najamuddin, Najamuddin; Wahab, Iswandi (Journal Omni-Akuatika, 2023)
The Halmahera Walking Shark (Hemiscyllium halmahera) is an endemic fish in the Halmahera Sea. This species is distributed and found in the Kao Bay sea. The International Union for Conservation of Nature (IUCN) data shows that the Halmahera Walking Shark is in the Near Threatened status. Protection is carried out to protect the population, therefore scientific data and information are needed. This study focuses on the biological structure of the Halmahera Walking Shark population in Kao Bay sea. Data collection was carried out exploratively in coral reef, seagrass, mangrove ecosystems and by-catch. Samples were taken for morphometric data, weight and sex. Morphometric data were analyzed to obtain cohorts, separation index, class intervals, length-weight relationships and condition factors of walking shark. The result were found to be 33 individuals (13 male and 20 female). Morphological characteristics based on morphometric variables found no significant differences. Analysis of the cohort of the Halmahera Walking Shark (H.halmahera) found 3 groups namely the juvenile, mature and old age phases. The separation index shows that individuals come from different populations based on length. Growth pattern of the Halmahera Walking Shark (H.halmahera) is negative allometric. The histogram of the frequency distribution between classes found small to large size structures with different relative frequency percentages. The condition factor found that the body proportions of the Halmahera Walking Shark (H.halmahera) were in the plump category. All of this information is important to provide scientific data specifications to population.Keywords : Endemism, Halmahera, Morphology, Island, Semi enclosed